The incidence and aetiology of acute kidney injury in children in Norway between 1999 and 2008. (15th August 2014) - Jenssen, Gaute Reier; Hovland, Eirik; Bangstad, Hans‐Jacob; Nygård, Karin; Vold, Line; Bjerre, Anna
Abstract Aim Primary acute kidney injury (AKI) is a direct cause of hospitalisation in children, but can also result from other conditions. There is limited information on the epidemiology of this condition. Our aim was to describe the national incidence rate and aetiology of acute kidney injury in children under the age of 16 in Norway from 1999 to 2008. Methods We carried out a retrospective study of medical records provided by all 18 of the paediatric hospital departments that specialise in treating paediatric patients with AKI. Results We identified 315 cases of AKI (53% male), with an estimated average annual incidence rate of 3.3 cases per 100 000 children and a median annual occurrence of 33 cases. Most cases (43%) were in children under five. We identified 53 aetiologies and classified these into 30 aetiological groups: 24% of the cases were prerenal (n = 75), 74% were intrinsic/renal (n = 234) and 2% were postrenal (n = 5). Nephritic syndromes was the major cause (44%) of AKI, followed by haemolytic‐uraemic syndrome (HUS) (15%). Conclusion Nephritic syndromes and HUS are the most common aetiologies of AKI in Norway. Although our results could indicate a low incidence of paediatric AKI in Norway, the lack of other national studies makes comparisons difficult.